Analysis of Fiqh Muamalah on the Discount Practice at Ibnu Ali Store, Pasean, and Its Implications for Potential Riba - Riyanto Wijaya; Nurul Imamah (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the discount practice at Ibnu Ali Store, Pasean, from the perspective of fiqh muamalah and to examine its implications regarding the potential existence of riba. This research employed an empirical legal research method with a qualitative approach. Primary data were collected through observations, interviews with the store owner, the storekeeper, and three consumers, as well as documentation. Secondary data were obtained from the Qur'an, Hadith, books on fiqh muamalah, the Compilation of Sharia Economic Law (KHES), Fatwas of the National Sharia Council-Indonesian Council of Ulama (DSN-MUI), and relevant scientific journals. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The results show that Ibnu Ali Store applies a buy one get one discount system to selected products, especially snacks and light foods, to attract consumers and increase sales. Consumers receive clear information about the promotion before completing the transaction. The findings indicate that the practice fulfills the essential elements of a valid sale contract in fiqh muamalah, including mutual consent, transparency, and certainty of the goods and prices. Furthermore, the study finds no indication of riba because the discount is not related to loan transactions, deferred payments, or unlawful additional benefits. The additional product is a promotional bonus voluntarily provided by the seller as part of the sales agreement. Therefore, the discount practice at Ibnu Ali Store is permissible under Islamic law, provided that it continues to uphold the principles of justice, honesty, transparency, and mutual consent in commercial transactions.